ÓZLESTIRMEWSHI OQÍWSHÍLARDÍŃ KOGNITIV TARAWÍNÍŃ PSIXOLOGIYALÍQ ÓZGESHELIKLERI - Sh.Sherimbetova, Z. (SCIENCE and SOCIETY, 2024)
The article talks about the psychological characteristics of the cognitive of non-assimilating students. Concepts about the characteristics of students' cognitive processes are presented.
Keywords: speaking; defects; vision; listing skill; mental retardation; adaptation; analysis